### (0) Obligation:

Runtime Complexity TRS:
The TRS R consists of the following rules:

f(nil) → nil
f(.(nil, y)) → .(nil, f(y))
f(.(.(x, y), z)) → f(.(x, .(y, z)))
g(nil) → nil
g(.(x, nil)) → .(g(x), nil)
g(.(x, .(y, z))) → g(.(.(x, y), z))

Rewrite Strategy: FULL

### (1) DecreasingLoopProof (EQUIVALENT transformation)

The following loop(s) give(s) rise to the lower bound Ω(n1):
The rewrite sequence
f(.(nil, y)) →+ .(nil, f(y))
gives rise to a decreasing loop by considering the right hand sides subterm at position [1].
The pumping substitution is [y / .(nil, y)].
The result substitution is [ ].

### (3) RenamingProof (EQUIVALENT transformation)

Renamed function symbols to avoid clashes with predefined symbol.

### (4) Obligation:

Runtime Complexity Relative TRS:
The TRS R consists of the following rules:

f(nil) → nil
f(.(nil, y)) → .(nil, f(y))
f(.(.(x, y), z)) → f(.(x, .(y, z)))
g(nil) → nil
g(.(x, nil)) → .(g(x), nil)
g(.(x, .(y, z))) → g(.(.(x, y), z))

S is empty.
Rewrite Strategy: FULL

Infered types.

### (6) Obligation:

TRS:
Rules:
f(nil) → nil
f(.(nil, y)) → .(nil, f(y))
f(.(.(x, y), z)) → f(.(x, .(y, z)))
g(nil) → nil
g(.(x, nil)) → .(g(x), nil)
g(.(x, .(y, z))) → g(.(.(x, y), z))

Types:
f :: nil:. → nil:.
nil :: nil:.
. :: nil:. → nil:. → nil:.
g :: nil:. → nil:.
hole_nil:.1_0 :: nil:.
gen_nil:.2_0 :: Nat → nil:.

### (7) OrderProof (LOWER BOUND(ID) transformation)

Heuristically decided to analyse the following defined symbols:
f, g

### (8) Obligation:

TRS:
Rules:
f(nil) → nil
f(.(nil, y)) → .(nil, f(y))
f(.(.(x, y), z)) → f(.(x, .(y, z)))
g(nil) → nil
g(.(x, nil)) → .(g(x), nil)
g(.(x, .(y, z))) → g(.(.(x, y), z))

Types:
f :: nil:. → nil:.
nil :: nil:.
. :: nil:. → nil:. → nil:.
g :: nil:. → nil:.
hole_nil:.1_0 :: nil:.
gen_nil:.2_0 :: Nat → nil:.

Generator Equations:
gen_nil:.2_0(0) ⇔ nil
gen_nil:.2_0(+(x, 1)) ⇔ .(nil, gen_nil:.2_0(x))

The following defined symbols remain to be analysed:
f, g

### (9) RewriteLemmaProof (LOWER BOUND(ID) transformation)

Proved the following rewrite lemma:
f(gen_nil:.2_0(n4_0)) → gen_nil:.2_0(n4_0), rt ∈ Ω(1 + n40)

Induction Base:
f(gen_nil:.2_0(0)) →RΩ(1)
nil

Induction Step:
f(gen_nil:.2_0(+(n4_0, 1))) →RΩ(1)
.(nil, f(gen_nil:.2_0(n4_0))) →IH
.(nil, gen_nil:.2_0(c5_0))

We have rt ∈ Ω(n1) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n).

### (11) Obligation:

TRS:
Rules:
f(nil) → nil
f(.(nil, y)) → .(nil, f(y))
f(.(.(x, y), z)) → f(.(x, .(y, z)))
g(nil) → nil
g(.(x, nil)) → .(g(x), nil)
g(.(x, .(y, z))) → g(.(.(x, y), z))

Types:
f :: nil:. → nil:.
nil :: nil:.
. :: nil:. → nil:. → nil:.
g :: nil:. → nil:.
hole_nil:.1_0 :: nil:.
gen_nil:.2_0 :: Nat → nil:.

Lemmas:
f(gen_nil:.2_0(n4_0)) → gen_nil:.2_0(n4_0), rt ∈ Ω(1 + n40)

Generator Equations:
gen_nil:.2_0(0) ⇔ nil
gen_nil:.2_0(+(x, 1)) ⇔ .(nil, gen_nil:.2_0(x))

The following defined symbols remain to be analysed:
g

### (12) NoRewriteLemmaProof (LOWER BOUND(ID) transformation)

Could not prove a rewrite lemma for the defined symbol g.

### (13) Obligation:

TRS:
Rules:
f(nil) → nil
f(.(nil, y)) → .(nil, f(y))
f(.(.(x, y), z)) → f(.(x, .(y, z)))
g(nil) → nil
g(.(x, nil)) → .(g(x), nil)
g(.(x, .(y, z))) → g(.(.(x, y), z))

Types:
f :: nil:. → nil:.
nil :: nil:.
. :: nil:. → nil:. → nil:.
g :: nil:. → nil:.
hole_nil:.1_0 :: nil:.
gen_nil:.2_0 :: Nat → nil:.

Lemmas:
f(gen_nil:.2_0(n4_0)) → gen_nil:.2_0(n4_0), rt ∈ Ω(1 + n40)

Generator Equations:
gen_nil:.2_0(0) ⇔ nil
gen_nil:.2_0(+(x, 1)) ⇔ .(nil, gen_nil:.2_0(x))

No more defined symbols left to analyse.

### (14) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
f(gen_nil:.2_0(n4_0)) → gen_nil:.2_0(n4_0), rt ∈ Ω(1 + n40)

### (16) Obligation:

TRS:
Rules:
f(nil) → nil
f(.(nil, y)) → .(nil, f(y))
f(.(.(x, y), z)) → f(.(x, .(y, z)))
g(nil) → nil
g(.(x, nil)) → .(g(x), nil)
g(.(x, .(y, z))) → g(.(.(x, y), z))

Types:
f :: nil:. → nil:.
nil :: nil:.
. :: nil:. → nil:. → nil:.
g :: nil:. → nil:.
hole_nil:.1_0 :: nil:.
gen_nil:.2_0 :: Nat → nil:.

Lemmas:
f(gen_nil:.2_0(n4_0)) → gen_nil:.2_0(n4_0), rt ∈ Ω(1 + n40)

Generator Equations:
gen_nil:.2_0(0) ⇔ nil
gen_nil:.2_0(+(x, 1)) ⇔ .(nil, gen_nil:.2_0(x))

No more defined symbols left to analyse.

### (17) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
f(gen_nil:.2_0(n4_0)) → gen_nil:.2_0(n4_0), rt ∈ Ω(1 + n40)